2002
DOI: 10.1128/jvi.76.20.10546-10552.2002
|View full text |Cite
|
Sign up to set email alerts
|

Insertions in the Reverse Transcriptase Increase both Drug Resistance and Viral Fitness in a Human Immunodeficiency Virus Type 1 Isolate Harboring the Multi-Nucleoside Reverse Transcriptase Inhibitor Resistance 69 Insertion Complex Mutation

Abstract: Recent studies have shown that the accumulation of multiple mutations associated with nucleoside reverse transcriptase inhibitor (NRTI) resistance may be grouped as multi-NRTI resistance (MNR) complexes. In this study, we have examined the viral fitness of recombinant viruses carrying the reverse transcriptase (RT) of a human immunodeficiency virus type 1 (HIV-1) primary isolate harboring mutations comprising the MNR 69 insertion complex. Different RT mutants were prepared in the sequence context of either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…We have shown that addition of mutations 210W, 211K, and 214F to the 41L/69S-XX/215Y combination partially repairs the defect in DNA chain elongation, suggesting that these mutations should improve viral replication fitness. Quiñones-Mateu et al (27) have recently reported that the removal of the 69S-SS mutations from the genome of a virus containing 69S-SS mutations in a background containing a variety of mutations, including AZT resistance mutations, produced a virus with reduced fitness. This result suggests that the contribution of the 69S-SS mutations to fitness depends on the mutational environment in the rest of the RT coding region.…”
mentioning
confidence: 99%
“…We have shown that addition of mutations 210W, 211K, and 214F to the 41L/69S-XX/215Y combination partially repairs the defect in DNA chain elongation, suggesting that these mutations should improve viral replication fitness. Quiñones-Mateu et al (27) have recently reported that the removal of the 69S-SS mutations from the genome of a virus containing 69S-SS mutations in a background containing a variety of mutations, including AZT resistance mutations, produced a virus with reduced fitness. This result suggests that the contribution of the 69S-SS mutations to fitness depends on the mutational environment in the rest of the RT coding region.…”
mentioning
confidence: 99%
“…The inserted dipeptide is most often SS or a variation thereof and is present in approximately 2% of NRTI-treated individuals (9,(42)(43)(44). The insert provides a certain level of drug resistance, but it also has a negative impact on viral replication fitness in the absence of drugs (37).…”
mentioning
confidence: 99%
“…These sets of primers and probes allowed subtype-specific PCR amplification and hybridization so that cross-hybridization between subtype B, A, and AE probes did not occur (30). A relative fitness value for each virus in the competition was estimated by using the production of each individual HIV-1 strain in the dual infection (24,25). A total relative fitness value was calculated as the average of the two relative fitness values corresponding to the competition between each subtype B HIV-1 isolate or recombinant virus and each of the nonsubtype B HIV-1 control strains.…”
mentioning
confidence: 99%